(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
This paper aims to illustrate the legal framework related to the right to food and food sovereignty in Nepal, highlighting some problematic aspects related to access to food. In particular, the paper focuses on provisions that aim to counteract land grabbing and seed biopiracy. The research reveals that in Nepal the concept of food sovereignty is considered equivalent to the right to food security and the right to be free from hunger.